Poster 168: Is Workload Associated with Internal Impingement in Professional Baseball Players? An Analysis of Days of Rest, Innings Pitched and Batters Faced. Issue 7 (30th July 2022) - Chalmers, Peter; Mcelheny, Kathryn; Dangelo, John; Ma, Kevin; Rowe, Dana; Erickson, Brandon
Objectives: The purpose of this study was to determine if number of days of rest between outings, number of innings pitched in each outing, number of batters faced in each outing, and being a starting pitcher are risk factors for internal impingement in professional baseball pitchers. Methods: All professional baseball pitchers who were diagnosed with internal impingement between 2011-2017 were identified using the Major League Baseball (MLB) Health and Injury Tracking System (HITS). A separate player usage dataset was used to determine workload. We then compared workload variables between pitcher-games 2, 6, 12, and >12 weeks prior to documented internal impingement to pitcher-games from a control group who were never diagnosed with internal impingement. In a paired analysis, we compared the acute workload (2, 6, 12 weeks) prior to injury to the injured pitcher's workload >12 weeks prior to injury. Results: There were 624 professional baseball pitchers who were documented in the MLB HITS database as having had internal impingement between 2011-2017. Across all time points, players with more innings pitched per game and more batters faced per game were associated with a higher incidence of subsequent internal impingement compared to controls. However, there were not significantly more innings pitched, more batters faced, or fewer days rest in the acute period (12 weeks) prior to injury when compared to baseline workload. Being a starting pitcher was associated with a higher incidence of internal impingement. Conclusions: Greater pitcher workload and being a starting pitcher were associated with increased risk for internal impingement in professional baseball players. However, this injury was not associated with an acute increase in workload, suggesting that internal impingement may be due to the cumulative effects of workload over a career. Table 1.